Digital Agricultural Knowledge Platform (IDEAL) using KOHA for National Agricultural Research and Education System - GUPTA, MANSI; KUMAR, AMRENDER; SHARMA, SHELLY; RANA, KAJOL; VERMA, NIDHI; PANDEY, P S; RATHORE, N S (The Indian Journal of Agricultural Sciences, 2022)
Digital libraries are equipped to provide access to multiple contents with potentially infinite number of resources to users. The libraries of the Indian National Agricultural Research and Education System (NARES) mainly the ICAR institutions and Agricultural Universities have a collection of huge literature of immense value available in various print and digital forms. These resources if made available at a single platform will go a long way in facilitating its sharing and minimizing the duplication efforts by the partner libraries. Realizing its importance, a requirement of a national level union catalog was felt to ensure single point access for the valuable information on the vast resources of NARES libraries. Information and Communication Technology (ICT) brought solution to a lot of challenging issues to all facets of the university system and the library is not an exemption. The Indian Digital Ensemble of Agricultural Libraries (IDEAL) is a customized platform for Agricultural Libraries of Indian National Agricultural Research and Education System (NARES) by adopting the KOHA-an open source integrated library management software for their routine operations in all libraries. KOHA is a software platform built on ‘Software as a Service’ (SaaS) concept to provide hassle free, ready to use based platform for sharing library holdings through a union catalogue as per the international standards. In this catalogue, the information can be shared at a single platform for all the users for example, students, researchers and faculties, extension workers and others. The system also provides search facilities through various parameters example, title, author, subject, number etc. The libraries of the State Agriculture Universities and its constituent colleges (SAUs) and ICAR institutes have been connected at a central server for its routine activities through IDEAL Platform. An online public access catalog (OPAC) of each library has been created, which provides easy and enhanced experience of accessing the library resources 24 × 7 to the users. This has greatly facilitated sharing and access of library resources among the NARES partners.